2016
DOI: 10.1016/j.envexpbot.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerant genes from halophytes are potential key players of salt tolerance in glycophytes

Abstract: Crop productivity strongly depends on several biotic and abiotic factors. Salinity is one of the most important abiotic factors, besides drought, extreme temperatures, light and metal stress. The enhanced burden of secondary salinization induced through anthropogenic activities increases pressure on glycophytic crop plants. The recent isolation and characterization of salt tolerance genes encoding signaling components from halophytes, which naturally grow in high salinity, has provided tools for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 241 publications
(304 reference statements)
2
126
0
Order By: Relevance
“…First, potential genes from halophytes can be identified and used as candidates for improving salt tolerance in glycophytes. This can be achieved either by overexpression of identified gene of interest (reviewed in Himabindu et al, ) or by random approach wherein a cDNA library from halophyte is expressed in glycophyte and then cDNA inserts are identified in lines showing increased salt tolerance (Rigo et al, ). Second, halophyte cultivation is practiced for desalinization of degraded soils (Table ) and recovery of value‐added products (Table ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…First, potential genes from halophytes can be identified and used as candidates for improving salt tolerance in glycophytes. This can be achieved either by overexpression of identified gene of interest (reviewed in Himabindu et al, ) or by random approach wherein a cDNA library from halophyte is expressed in glycophyte and then cDNA inserts are identified in lines showing increased salt tolerance (Rigo et al, ). Second, halophyte cultivation is practiced for desalinization of degraded soils (Table ) and recovery of value‐added products (Table ).…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…Therefore, proline‐overproduction synthesis genes are a good way to enhance plant stress resistance. Our series of studies has shown that this way is applicable (Himabindu et al, ; Wang et al, ; Xu et al, ; Yan et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Currently, more than one third of the world's arable land is subjected to soil quality, and land degradation due to salt stress and agricultural yield has greatly decreased (Fan et al, ; Gao et al, ; Li et al, ; Tilman, Balzer, Hill, & Befort, ). Additionally, the salt‐affected area is increasing at a rate of 10% yearly because of high evaporation, low rainfall, inadequate irrigation, and other irrational anthropogenic activity (Himabindu et al, ; Liu et al, ; Mose et al, ). By 2050, the salinized area will exceed 50% of global arable land (Liu et al, ; Mao, Kang, et al, ; Mao, Zhang, et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adaptations are expressed in traits that can be used as potential selection criteria in breeding programmes for salinity tolerance. Several authors have suggested potential uses of various halophyte species, such as forage (Ashraf et al, 2006;Glenn et al, 2013;Panta et al, 2014;Rogers et al, 2005), oil production (Glenn et al, 2013;Weber, Ansari, Gul, & Khan, 2007), biodiesel production (McDowell Bomani, Bulzan, Centeno-Gomez, & Hendricks, 2009), human consumption (Barreira et al, 2017;Panta et al, 2014), soil phytoremediation (Shabala, 2013) and the use of known genes that improve the stress resistance of major crops (Ahanger et al, 2017;Himabindu et al, 2016). These studies reveal interesting possibilities for the use of these species for the development of technologies and salt-tolerant crops.…”
mentioning
confidence: 99%